2007
DOI: 10.1042/bj20070089
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome-proliferator-activated receptors and the control of levels of prostaglandin-endoperoxide synthase 2 by arachidonic acid in the bovine uterus

Abstract: Arachidonic acid is a potential paracrine agent released by the uterine endometrial epithelium to induce PTGS2 [PG (prostaglandin)-endoperoxide synthase 2] in the stroma. In the present study, bovine endometrial stromal cells were used to determine whether PTGS2 is induced by arachidonic acid in stromal cells, and to investigate the potential role of PPARs (peroxisome-proliferator-activated receptors) in this effect. Arachidonic acid increased PTGS2 levels up to 7.5-fold within 6 h. The cells expressed PPARalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Increased production of PG in various tissues after stimulation by polyunsaturated fatty acids has been previously reported in rat uterine stromal cells [49] and in endometrial cells from the late-pregnant ewes [25]. In our study, AA increased levels of COX-2 and cPLA 2 after 48 hours of incubation and these results were in agreement with what previously shown in bovine endometrial cells [50]. These observations suggest tissue and cell-specific differences in the induction of cPLA 2 by AA and support a new vision of the importance of AA in the synthesis of PGE 2 .…”
Section: Discussionsupporting
confidence: 96%
“…Increased production of PG in various tissues after stimulation by polyunsaturated fatty acids has been previously reported in rat uterine stromal cells [49] and in endometrial cells from the late-pregnant ewes [25]. In our study, AA increased levels of COX-2 and cPLA 2 after 48 hours of incubation and these results were in agreement with what previously shown in bovine endometrial cells [50]. These observations suggest tissue and cell-specific differences in the induction of cPLA 2 by AA and support a new vision of the importance of AA in the synthesis of PGE 2 .…”
Section: Discussionsupporting
confidence: 96%
“…MG-132 (47,69,70) In vitro, EEC Y IL-6 and LIF In vitro, bovine ESC Y PTGS-2 and COX-2 Parthenolide (69) In vitro, bovine ESC Y PTGS-2 SN-50 (33,47) In vitro, EEC Y IL-6 and LIF In vivo, nude mouse a Y Ec lesion development Y ICAM-1 and [ apoptosis Curcumin (53,54,67,168) In vitro, ESC and EcSC Y MIF In vivo, human Unknown, Y symptoms? Sulindac (55) In vitro, ESC Y RANTES Thalidomide (62) In vitro, EcSC Y IL-8 TPCK (59) In vitro, EcSC Y IL-8 GnRH-a (59) In vivo, human/in vitro, EcSC b…”
Section: Nf-kb Inhibitor Experimental Model Effectsmentioning
confidence: 96%
“…In vitro, EcCs have shown IL-1b, TNF-a, or LPS-dependent NF-kB activation, positively modulating the proinflammatory cytokines RANTES, MIF, IL-8, IL-6, TNF-a, ICAM-1, granulocyte macrophage-colony-stimulating factor (GM-CSF), and monocyte chemoattractant protein-1 (MCP-1) (58-61, 64, 65, 67, 68). Possibly COX-2 could also be modulated by NF-kB, as evidenced in bovine ECs (69,70). In endothelial cells, NF-kB activity has been associated with vascular cell adhesion molecule-1 (VCAM-1), ICAM-1, and…”
Section: Nf-kb and The Endometriosis-associated Inflammatory Responsementioning
confidence: 98%
“…Several in vitro studies using synthetic agonists have demonstrated that activation of PPAR isotypes (except gamma) affects fertility by increasing the expression and/or production of prostaglandins, for example, prostaglandin (PG) F2 α , and PGE2 in bovine endometrial cells [44, 77]. Other in vitro studies were carried out in order to test the response to PPAR isotypes in two bovine cell lines (MDBK and MAC-T) with the purpose of determining PPAR α and PPAR γ target genes [26, 28, 36, 61].…”
Section: Ruminant Ppar Response To Synthetic and Natural Agonistsmentioning
confidence: 99%